Efficacy of Extraction and Microencapsulation of Betacyanin extracted and Freeze-Dried from Red Dragon Fruit (Hylocereus polyrhizus) Peel - N. P. Minh (Journal of Global Pharma Technology, 2019)
Microencapsulation is utilized to prevent chemically sensitive bioactive components from degradation due to harsh environmental conditions and is also applicable to handle the emission of the encapsulate. One of the key factors to be considered in the microencapsulation process is the coating material.  Dragon fruit peel derived from processing companies contains an abundant of betacyanin, a valuable pigment. In our research, different parameters of solvent extraction (kind of solvent, pH, ratio of solvent: material); microencapsulation (kind and concentration of coating agent, synergistic effect of combined coating agents) were thoroughly investigated. Our results showed that betacyanin can achieve the highest yield by extraction with water at pH 5.0 with dissolving ratio 5.5: 1.0 (water: material) within 8 hours at ambient temperature. The filtrates were then mixed with 20% maltodextrin+10% β-cyclodextrin as microencapsulating agent during the freeze-drying to get dried powder (6.5% moisture content). By this approach, the highest betacyanin could be maintained at utmost level.Keywords: Dragon fruit peel, Betacyanin, Extraction, Microencapsulation, Maltodextrin, β-cyclodextrin.